Brief Report: Chikungunya Viral Arthritis in the United States: A Mimic of Seronegative Rheumatoid Arthritis. Issue 5 (May 2015) - Miner, Jonathan J.; Aw Yeang, Han Xian; Fox, Julie M.; Taffner, Samantha; Malkova, Olga N.; Oh, Stephen T.; Kim, Alfred H. J.; Diamond, Michael S.; Lenschow, Deborah J.; Yokoyama, Wayne M.
<x xml:space="preserve">Abstract</x> Objective Chikungunya virus (CHIKV) is an arthritogenic mosquito‐transmitted alphavirus that spread to the Caribbean in 2013 and to the US in 2014. CHIKV‐infected patients develop inflammatory arthritis that can persist for months or years, but little is known about the rheumatologic and immunologic features of CHIKV‐related arthritis in humans, particularly as compared to rheumatoid arthritis (RA). The purpose of this study was to describe these features in a group of 10 American travelers who were nearly simultaneously infected while visiting Haiti in June 2014. Methods Patient history was obtained and physical examination and laboratory tests were performed. All patients with CHIKV‐related arthritis had detectable levels of anti‐CHIKV IgG. Using cytometry by time‐of‐flight (CyTOF), we analyzed peripheral blood mononuclear cells in CHIKV‐infected patients, healthy controls, and patients with untreated, active RA. Results Among 10 CHIKV‐infected individuals, 8 developed persistent symmetric polyarthritis that met the American College of Rheumatology/European League Against Rheumatism 2010 criteria for (seronegative) RA. CyTOF analysis revealed that RA and CHIKV‐infected patients had greater percentages of activated and effector CD4+ and CD8+ T cells than healthy controls. Conclusion In addition to similar clinical features, patients with CHIKV infection and patients with RA develop very similar peripheral T cell phenotypes. These overlapping clinical and immunologic features highlight a need for rheumatologists to consider CHIKV infection when evaluating patients with new, symmetric polyarthritis.